1994
DOI: 10.1111/j.1365-2141.1994.tb04930.x
|View full text |Cite
|
Sign up to set email alerts
|

Myelodysplasia in a patient with pre‐existing paroxysmal nocturnal haemoglobinuria: a clonal disease originating from within a clonal disease

Abstract: Paroxysmal nocturnal haemoglobinuria (PNH) is an acquired haemolytic anaemia, clonal in nature, due to somatic mutation. PNH may evolve to aplastic anaemia; more rarely to a myelodysplastic syndrome (MDS) or to acute myeloid leukaemia (AML). We have studied a patient who suffered from PNH and later developed refractory anaemia with ringed sideroblasts (RARS) associated with trisomy 8. By testing peripheral blood cells with appropriate antibodies we have shown that all of the red cells, neutrophils and monocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 8 publications
1
18
0
1
Order By: Relevance
“…However, from the available data in the literature, PNH can be regarded as a preleukaemic lesion. FISH analysis of previous cases showed that the MDS clone must have arisen from within the PNH clone, and the karyotypic change of the MDS clone took place in a cell that was less multipotent than that from which the PNH clone arose (Longo et al, 1994). In our case it seems that either different clones were simultaneously affected by genetic lesions or the PNH clone was developed later in the course of the disease.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…However, from the available data in the literature, PNH can be regarded as a preleukaemic lesion. FISH analysis of previous cases showed that the MDS clone must have arisen from within the PNH clone, and the karyotypic change of the MDS clone took place in a cell that was less multipotent than that from which the PNH clone arose (Longo et al, 1994). In our case it seems that either different clones were simultaneously affected by genetic lesions or the PNH clone was developed later in the course of the disease.…”
Section: Discussionmentioning
confidence: 49%
“…In the literature, two cases of trisomy 8 have been reported in association with PNH (Longo et al, 1994;Parlier et al, 1992). The patient reported proves that the bone marrow cells were generally prone to somatic mutations and myelodysplasia did not evolve from the PNH clone.…”
Section: Discussionmentioning
confidence: 75%
“…A review of literature presents confl icting views. Van Kamp et al documented presence of GPI anchored proteins on MDS cells whereas Nakahata et al and Longo et al demonstrated that the leukemic blasts arose from GPI anchored defi cient cells [7][8][9]. The majority of neutrophils in our case were dysplastic which also lacked GPI anchored proteins, thus favoring a common pathogenetic origin of myelodysplastic and PNH clone.…”
Section: Discussionmentioning
confidence: 64%
“…However, no translocation was detected, demonstrating that this event is not common in PNH. In patients with concomitant PNH and MDS, other studies have found trisomy 8 in the fraction of GPI-deficient cells, suggesting that the PIGA mutation affected the stem cell first, and chromosomal aberrations evolved within a subclone thereafter [5,33,34]. Recently, it was shown that a stochastic model of clonal stem cell evolution could capture some of the features of PNH [35].…”
Section: Discussionmentioning
confidence: 99%